Nghiên cứu tổng hợp xúc tác lai tạp dùng cho phản ứng đồng phân hóa n-hexan - Tùng, Lê Thanh; Thu, Hoa Hữu (Vietnam Journal of Chemistry, 2014)
A series of hybrid catalysts PtWZr/PtSZr, PtWZr/H-ZSM5 and PtWZr/HPA was been prepared. The structure and the surface property of the hybrid catalysts obtained were characterized by using different methods physical such as XRD, SEM, TEM, BET, NH3-TPD. Their catalytic activity in n-hexan isomerization was tested by MAT5000 showed that the conversion of this reation on catalysts is from 48,97% to 52,01%, selectivity is from 86,73% to 98,5% and that their stability of catalysts is high.